Diabetic ketoacidosis with sepsis complicated by central pontinemyelinolysis: A case report - Kata, Srinivasa Rajasekhar; Patnala , Sai Lavanya; Kande, Venkata Abhishek; Dosakayala, Bhuvana; Mummadireddy, Sivani (Indian Journal of Case Reports, 2026)
Diabetic ketoacidosis (DKA) is a condition characterized by high blood sugar, elevated ketone bodies, and acidosis.Central pontine myelinolysis (CPM) is a severe demyelinating syndrome that can be life-threatening. The associationbetween CPM and DKA is very less reported in the medical literature. In this case, a 22-year-old female presentedwith new-onset diabetes and developed DKA, which was managed with aggressive fluid resuscitation and sodiumbicarbonate infusion. However, the patient subsequently experienced loss of consciousness and altered mental status. Further examination revealed altered serum sodium levels and positive urinary ketones. Brain magnetic resonanceimaging (MRI) showed cerebral edema and abnormal signal intensity in the medulla and central pons. Supportive therapy was initiated, and over the next few weeks, the patient gradually regained consciousness and muscle strength.Follow-up after 5 months showed complete resolution of symptoms and no residual damage on MRI. The exact mechanism underlying the development of CPM while managing DKA remains unclear, although it is hypothesized to be related to a rapid hypertonic insult. This case highlights the importance of recognizing and managing this rare complication in patients with DKA.